Partisipasi Masyarakat dalam Program Pertanian Perkotaan pada Penghuni Rumah Susun Marunda, Jakarta Utara - Riska Rahma Arriani; Mardwi Rahdriawan (Teknik PWK (Perencanaan Wilayah Kota), 2019)
The Urban Farming Program in the Rusun Marunda was initiated by the government and managed by 50 farmers in 2014. The goals of the urban farming program are to develop green space, to provide the food access system and to empower the  community. However, the number of farmers who participate in Urban Farming Program continues to decrease as in 2019 only remains 5 (five) farmers. This research aims to find out the decreasing reasons for ommunity participation in Urban Farming Program. The method of this research uses the qualitative approach with purposive sampling. This study found that the reasons for farmers’ participation in Urban Farming Program are driven by two different motivations; psychological-Altruism motivation and economic-egoism motivation. Farmers with psychology-Altruism motivation are participating due to fulfill self-satisfaction while farmers with economic motivation are participating due to gain the financial benefits from Urban Farming Program. The results of the study found out that the decreasing number in community participation is caused by the obstacles in farming which demotivating farmers to participate in the Urban Farming Program. As a result, Farmers with economic-egoism motivation refuse to participate while farmers with psychological motivation still participate in Urban Farming Program.